2015
DOI: 10.17352/2455-4634.000005
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of S. mutans and S. sorbinus in Caries Active and Caries Free Children by PCR Approach

Abstract: Background: Streptococcus mutans (S. mutans) and Streptococcus sorbinus (S. sorbinus) have been considered to be the most important micro-organisms associated with dental caries. Therefore, purpose of this study is to detect and correlate the presence of S. mutans and S. sobrinus in the dental plaque of caries free and caries active children, by using Polymerase chain reaction (PCR) method. Materials and Methods:Twenty patients aged between ages 4-8 years were included in the study. The subjects were divided i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 30 publications
2
7
1
1
Order By: Relevance
“…There are intriguing aspects of caries etiology that have not been adequately explored. One of those is potential synergy between S. mutans and S. sobrinus as caries experience tends to be worse when both are isolated from carious lesions [ 54 56 ]. Another is the contribution of non-MS low pH streptococci which may be among primary plaque colonizers, numerically dominant to the MS (potentially addressing the concern about proportional representation of the MS) and able to set the stage for the ascension of stronger cariogens [ 8 , 57 ].…”
Section: Is An All-encompassing Hypothesis Of Caries Etiology Necessamentioning
confidence: 99%
“…There are intriguing aspects of caries etiology that have not been adequately explored. One of those is potential synergy between S. mutans and S. sobrinus as caries experience tends to be worse when both are isolated from carious lesions [ 54 56 ]. Another is the contribution of non-MS low pH streptococci which may be among primary plaque colonizers, numerically dominant to the MS (potentially addressing the concern about proportional representation of the MS) and able to set the stage for the ascension of stronger cariogens [ 8 , 57 ].…”
Section: Is An All-encompassing Hypothesis Of Caries Etiology Necessamentioning
confidence: 99%
“… 4 , 16 Although the etiology of ECC is multifactorial, S. mutans and S. sobrinus play a key role. 3 Children with ECC were included in the current study, as the acquisition of MS has been found to be more common during the window period that occurs around the age of 26 months. 7 Thus for a thorough caries prediction and its subsequent treatment, detection of the presence of MS in early years is important.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have been conducted to understand the association between caries activity and microorganisms, the results of which have revealed children with elevated counts of S. mutans and S. sobrinus have a higher incidence of dental caries. 3 , 5 , 6 , 17 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Některých studií se účastnily výhradně děti a ve výsledcích bylo poukázáno na fakt, že jedinci, kteří mají v ústech přítomny bakterie rodu Streptococcus mutans, mají také větší počet aktivně probíhajících kariézních lézí. Ke zhodnocení stavu chrupu bylo využito klinického vyšetření a v indikovaných případech také rentgenových snímků [14]. Samotné testování přímo pomocí sady GC Saliva-Check Mutans (GC Europe, Leuven N. V., Belgie) bylo zahrnuto zatím jen v několika málo studiích, které však potvrdily vhodnost jednoduchého testu pro určení zvýšené Cílem naší studie bylo prokázat vliv bakterie Streptococcus mutans na stav chrupu u dvou skupin pacientů, a to u mladých dospělých s relativně sanovaným chrupem a u starších pacientů s částečnými snímatelnými náhradami.…”
Section: Abstract: Dental Caries -Streptococcus Mutans -Saliva -Carieunclassified